A pilot randomized clinical trial of the Skills to Enhance Positivity (STEP) group intervention for young adults with depression: Examining feasibility and acceptability - Katherine M. Tezanos; Natalia Macrynikola; Leanna Villareal; Jackson Doerr; Nazaret Suazo; Laura Whiteley; Shirley Yen (PLoS ONE, 2026)
Addressing the pressing concern of rising rates of depression and suicide in young adults, the present study explores the feasibility of adapting the Skills to Enhance Positivity (STEP) intervention as a group-based program in a community mental health setting in the United States. STEP is an adjunctive intervention designed to enhance positive emotions to reduce suicide risk and alleviate depressive symptoms. Fifty-two participants aged 18–26 ( M = 21.40, SD = 2.00) were randomized to receive group-based STEP or enhanced treatment as usual (ETAU). The group-based STEP format was well-received, with high attendance and positive feedback, demonstrating feasibility and acceptability. While underpowered to detect between-group differences, at post-intervention and follow-up, those in STEP exhibited increases in positive emotions and significant reductions in depression and suicidal ideation. These changes were larger compared to the effect sizes from those in ETAU. These findings underscore the potential of the adapted STEP model to help young adults, warranting further exploration in larger trials. Study is registered on clinicaltrails.gov under ID Number: NCT06621992.